Sex-Related Differences in Glioblastoma: A Single-Center Retrospective Cohort Study - Chiara Prosperetti; Meltem Yenigün; Alberto Pagnamenta; Payam Tabaee Damavandi; Giulio Disanto; Francesco Marchi; Vittoria Espeli; Barbara Muoio; Paolo Spina; Gianfranco Pesce; Pamela Agazzi (Biomedicines, 2025)
Background: Sex differences play a significant role in the epidemiology, biology, and outcomes of many cancers, including glioblastoma (GB), the most common and aggressive primary brain tumor. GB is more frequent in males, while females tend to have longer survival, though the underlying reasons for these differences remain poorly understood. Potential contributors include hormonal influences, sex-specific risk factors, and treatment disparities. Understanding these differences is critical for optimizing personalized treatment strategies. Methods: We conducted a retrospective analysis of patients with gliomas from a neuro-oncological database, with a primary focus on GB cases. Variables collected included sex, age, tumor type, molecular biomarker, and treatment modalities. The primary objective was to assess sex-based differences in tumor characteristics and outcomes, while the secondary objective was to identify predictors of time to progression and mortality. Results: The cohort comprised 125 GB, 48 astrocytomas, and 16 oligodendrogliomas, with no significant sex-based differences in age or tumor type distribution. Among GB patients, multifocality was more prevalent in females (14% vs. 8%; p = 0.01); also, EGFR amplification was more frequent in females (25.5% vs. 52.5%; p = 0.007). Males received chemotherapy (80% vs. 63%; p = 0.04) and radiotherapy (84% vs. 67%; p = 0.03) more frequently than females. Survival was positively associated with MGMT methylation (p = 0.002) and negatively associated with TERT mutation (p = 0.01). Multivariable analysis identified TERT mutation as a predictor of increased mortality (HR = 4.1; 95% CI: 1.2–14; p = 0.025), while multifocality predicted both mortality (HR = 2.3; 95% CI: 1.3–3.9; p = 0.003) and reduced time to progression (HR = 3.3; 95% CI: 1.02–10.6; p = 0.04). Conclusions: This study underscores the importance of sex and molecular profiling in GB management, revealing distinct patterns in tumor characteristics and treatment administration between males and females. Our findings advocate for the integration of sex-specific considerations and molecular profiling into clinical decision-making to improve outcomes for GB patients.